2006
DOI: 10.1038/sj.onc.1209736
|View full text |Cite
|
Sign up to set email alerts
|

The retinoblastoma gene is involved in multiple aspects of stem cell biology

Abstract: Genetic programs controlling self-renewal and multipotentiality of stem cells have overlapping pathways with cell cycle regulation. Components of cell cycle machinery can play a key role in regulating stem cell self-renewal, proliferation, differentiation and aging. Among the negative regulators of cell cycle progression, the RB family members play a prominent role in controlling several aspects of stem cell biology. Stem cells contribute to tissue homeostasis and must have molecular mechanisms that prevent se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 53 publications
2
57
0
Order By: Relevance
“…RB and P53 pathways are involved in biological effects induced by BRG1 silencing RB and P53 pathways are part of the core circuitry that controls cell cycle arrest, differentiation, apoptosis and/or senescence (Galderisi et al, 2006;Campisi and d'Adda di Fagagna, 2007;Oberdoerffer and Sinclair, 2007). Several reports showed that BRG1 operates through regulation of these key cellular pathways (Strobeck et al, 2000;Lee et al, 2002;Hendricks et al, 2004;Kang et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RB and P53 pathways are involved in biological effects induced by BRG1 silencing RB and P53 pathways are part of the core circuitry that controls cell cycle arrest, differentiation, apoptosis and/or senescence (Galderisi et al, 2006;Campisi and d'Adda di Fagagna, 2007;Oberdoerffer and Sinclair, 2007). Several reports showed that BRG1 operates through regulation of these key cellular pathways (Strobeck et al, 2000;Lee et al, 2002;Hendricks et al, 2004;Kang et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the H2AX activation and the upregulation in the expression BRG1, RB and P53 crosstalk Several reports suggested that BRG1 binds to and regulates the retinoblastoma protein and the tumor suppressor protein p53 (Strobeck et al, 2000;Lee et al, 2002;Hendricks et al, 2004;Kang et al, 2004). These are master genes that control cell cycle arrest, differentiation, apoptosis and/or senescence (Felsani et al, 2006;Galderisi et al, 2006;Campisi and d'Adda di Fagagna, 2007;Oberdoerffer and Sinclair, 2007). We tried to evaluate whether the biological effects of BRG1 silencing were related to RB-and P53-related pathways.…”
Section: Genes Involved In Dna Repairmentioning
confidence: 99%
“…13,14 On the contrary, our previous findings demonstrated that MSC lacking RB1 expression showed a decline in proliferation and accumulation of DNA damage. This impairs stem cell properties with an increase in senescence.…”
Section: Introductionmentioning
confidence: 75%
“…This is in contrast with reports of other cell types including fibroblasts that showed strong resistance to cell cycle exit and uncontrolled proliferation following RB1 ablation. 13,14 Nevertheless, there are findings showing that RB1 may be dispensable for cell cycle exit and control of cell growth because it occurs in cardiomyocytes and pancreatic ß-cells. 19,20 Altogether these studies clearly show that RB1 function is context dependent, in some settings RB1, RB2/P130, and P107 can compensate for each other.…”
Section: Discussionmentioning
confidence: 99%
“…Although Rb is involved in multiple aspects of stem cell biology (Galderisi et al, 2006), its contribution in early hematopoiesis remains unclear. For example, it has been reported that Rb is dispensable for self-renewal and multilineage differentiation of adult hematopoietic stem cells (Walkley and Orkin, 2006).…”
mentioning
confidence: 99%